Sustainable living neighbourhoods: Measuring public space quality and walking environment in Lisbon - Teresa Santos; Filipa Ramalhete; Rui Pedro Julião; Nuno Pires Soares (Geography and Sustainability, 2022)
Obesity and global warming are two major challenges that affect communities’ health and quality of life. Providing good walking environments, with appropriate pedestrian infrastructure, green areas and access to commercial retail and transport hubs favour liveable, healthy, and sustainable cities. The Lisbon City Hall has implemented an intervention program in the public space as a strategy to improve environmental quality and mitigate the effects of climate change. The program “A square in each neighbourhood” intends not only to reinforce the economic base of Lisbon, namely tourism, restaurants, commerce, and creative activities but also to promote physical activity and improve the quality of living of all citizens. For studying the impact of the public space quality on the walking environment, Campolide, a typical Lisbon neighbourhood, Portugal, which includes one of the requalified squares, was selected. A two-step methodology based on spatial modelling is proposed. In the first step, the public space quality was evaluated based on a set of 13 urban quality attributes. Attributes, intended for the street level, were collected from open data platforms and complemented with a field survey. Then, through spatial analysis, these attributes were used to build the Pedestrian Environment Quality Indicator and the Priority Intervention Indicator. Using these indicators, walking-friendly streets were mapped and the most critical sites that require priority intervention were identified to prepare for the requalification planning process. The street with the highest quality in the study area according to the dimensions evaluated - connectivity, convenience, comfort, cleanliness, and conviviality - has a great offer of trees, bus stops, commercial establishments, commercial diversity, crossings, paper bins/eco points and esplanades. On the opposite side of the rank, the street with the lowest quality has no trees or green areas, transport stops, benches and tables, or commercial activity. The urban quality indicators constitute a helpful tool for city planners and policymakers when planning sustainable living neighbourhoods.